2006
DOI: 10.1177/1555412006290443
|View full text |Cite
|
Sign up to set email alerts
|

Hybrid Reality Games Reframed

Abstract: Hybrid reality games (HRGs) employ mobile technologies and GPS devices as tools for transforming physical spaces into interactive game boards. Rather than situating participants in simulated environments, which mimic the physical world, HRGs make use of physical world immersion by merging physical and digital spaces. Online multiuser environments already connect users who do not share contiguous spaces. With mobile devices, players may additionally incorporate interactions with the surrounding physical space. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
27
0
2

Year Published

2008
2008
2021
2021

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 75 publications
(29 citation statements)
references
References 34 publications
(34 reference statements)
0
27
0
2
Order By: Relevance
“…Choi and Hannafin (1993) expand on this by stating that the theoretical underpinnings of situated cognition center on the role of context, content, facilitation, and assessment. Further research (e.g., de Souze e Silva & Delacruz, 2006;Klabbers, 2006;Squire, 2005) has continued to support this idea.…”
Section: What Makes a Game An Instructional Gamementioning
confidence: 69%
See 1 more Smart Citation
“…Choi and Hannafin (1993) expand on this by stating that the theoretical underpinnings of situated cognition center on the role of context, content, facilitation, and assessment. Further research (e.g., de Souze e Silva & Delacruz, 2006;Klabbers, 2006;Squire, 2005) has continued to support this idea.…”
Section: What Makes a Game An Instructional Gamementioning
confidence: 69%
“…LARPs are usually set in a virtual context of fictional reality, and game play is governed or supervised by a game master (the instructor or facilitator). Hybrid reality games transform physical spaces into interactive game boards (de Souza e Silva & Delacruz, 2006). They make use of the physical context by merging the physical world and digital spaces.…”
Section: Serious Gamesmentioning
confidence: 99%
“…El grupo ISI de la Universidad de Málaga, proponen dos aplicaciones para la didáctica musical, en una de ellas proponen un piano virtual, que al colocar los dedos sobre el teclado virtual, la tecla que se oculta por el dedo reproduce el sonido de la tecla, en la otra se propone un pentagrama virtual, sobre el que los alumnos colocarán las notas virtuales (Peula, Zumaquero, Urdiales, Barbancho, & Sandoval, 2007). Otros trabajos de RA dentro de este campo los podemos encontrar descritos en (Bobick, Davis, & Intille, 1997), (Bobick, y otros, 1999), (Billinghurst, Kato, & Poupyrev, 2001), (Cheok, y otros, 2002), (Cheok, y otros, 2006), (De Souza e Silva & Delacruz, 2006), (Garzotto & Forfori, 2006).…”
unclassified
“…De Souza [2] has observed that location based game activities produce learning that is social, experiential and situated. Learning, however, is related to the objectives of the game designers.…”
Section: Introductionmentioning
confidence: 99%